The Modular Design of Turn-milling CNC for Special Stones - Yuhou Wu; Dehong Zhao; Xuan Mu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Stone products' processing technologies, processes and types have essential differences with metal's, which makes the traditional machine design method can not perform well in the design of processing equipment for special shaped stones. A new design method was used in this paper, which through the establishment of stone typical products and tool mathematical model. The needs of the motion axes was solved by kinematics equations application and the feasible design scheme of the machine tool's function was established. Thus, a new turn-milling combined NC machine tools, which have 8 movement axis and Double 5 axis linkage processing function is designed. Its modular structure design can meet the needs of the most stone material processing.  DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2560